Can PSMA PET/CT help in dose-tailoring in post-prostatectomy radiotherapy? - Champion, Ambroise; Zwhalen, Daniel Rudolf; Oehler, Christoph; Taussky, Daniel; Kroeze, Stephanie G. C.; Burger, Irene A.; Benzaquen, David (Frontiers in Oncology, 2023)
There are few randomized trials to evaluate the use of PSMA-PET in the planning of post-prostatectomy radiotherapy. There are two unresolved questions 1) should we increase the dose to lesions visible on PSMA-PET 2) can we reduce dose in the case of a negative PSMA-PET. In this review, we summarize and discuss the available evidence in the literature. We found that in general, there seems to be an advantage for dose-increase, but ta large recent study from the pre-PSMA era didn’t show an advantage for dose escalation. Retrospective studies have shown that conventional doses to PSMA-PET-positive lesions seem sufficient. On the other hand, in the case of a negative PSMA-PET, there is no evidence that dose-reduction is possible. In the future, the combination of PSMA-PET with genomic classifiers could help in better identify patients who might benefit from either dose- de-or -increase. We further need to identify intraindividual references to help identify lesions with higher aggressiveness.